Leadership communication, employee engagement, and online communication behaviors during crises: evidence from Jordanian universities - Alsharairi, Ahmad; Alazzah, Malik; Safori, Amjad; Aladwan, Muhammad Noor Saleh (Frontiers in Communication, 2025)
University institutions are being put to the test by crises, particularly when social media presents both positive and negative perspectives. This study examines the impact of leadership communication style on employees’ online communication behaviors and employee engagement at Jordanian institutions during times of crisis. This study develops an integrated framework that combines relational and situational perspectives to explain employee communication behavior. It is based on social exchange theory and situational crisis communication theory. A cross-sectional survey was conducted among 426 academic and administrative employees from six Jordanian institutions to collect data, which was then analyzed using SmartPLS (SEM). Results show that a leader’s communication style improves employee engagement by promoting good social media behaviors while stifling those that are adverse, such as disseminating rumors and public complaints. It emerged that employee engagement becomes the primary mechanism by which leadership’s communication exerts an effect on employee digital voice during times of crisis. In addition to enhancing situational crisis communication theory by introducing employees as proactive digital ambassadors in organizational crisis planning, the research makes theoretical contributions by using social exchange theory to show how leader-employee exchanges in reciprocity are transformed into online behaviors.